Class Analysis of Changing Patterns of Leisure in Urban Space under the Influence of Cyberspace in Isfahan - Mozhgan Pirak; Vahid Ghasemi; Masoud Kianpour (توسعه اجتماعی, 2021)
The importance of cyberspace (Internet and social networks) in today's human life is undeniable. As it has overshadowed all the different areas of people's lives. Leisure patterns are one of these aspects. Therefore, the main purpose of this study is to investigate the changes that have occurred in these patterns under the influence of cyberspace. Research presents the relationship between these two variables in the form of class analysis. For this purpose, 330 people in Isfahan were studied using a quantitative method. The data collection tool was a researcher-made questionnaire that was distributed among the three social classes of upper, middle and lower in the age range of 20-60 years. The validity of the questionnaire was formal and was confirmed by a group of experienced professors and experts. The reliability of the questionnaire was calculated using Cronbach's alpha coefficient, which was higher than the desired level (0.70) for all dimensions. Findings show that cyberspace has affected leisure patterns. Thus, leisure patterns have changed from being active, being collective, being real, self-fulfilling, to becoming passive, individualized, virtual, and deviant. Another important result of the research is the confirmation of class adjustment. Thus, the class has influenced the mechanism of influence between cyberspace and leisure-based patterns of active / passive, collective individual, and virtual / real. The mechanism of this effect was the same in the upper and lower classes, but in the middle class it was less intense and different from the other two classes.